Does Financial Technology and Financial Literacy Enhance Financial Inclusion? (Evidence from Several Countries) - Fenti Fitriani; Fitri Santi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to examine whether there is a relationship between financial literacy and financial technology with financial inclusion. Financial literacy in this context encompasses aspects of knowledge, skills, financial aspects, financial management, and access to financial knowledge. Meanwhile, financial technology includes digital financial services, financial behavioral intentions, and digital financial access. Financial inclusion covers financial stability, financial services, and digital finance. The methodology used in this research is qualitative research using literature studies, which include samples and data from 96 reputable international journals. The research was conducted from October until completion. The results of this study indicate that financial literacy and financial technology have a significant influence on financial inclusion.